Soft Information Acquisition And Transfer In The Small And Medium Enterprise (Sme) Lending Process: A Study Of Commercial Banks In Kenya - Ollows, Lilian; Moro, Andrea; Waweru, Freshia Mugo- (Archives of Business Research, 2018)
Soft information use in SME lending has been well established and more so when commercial banks employ the relationship lending methodology. Relationship lending implies that lenders rely on soft information in making a lending decision. This “soft” data such as information about management skills, management ethics and moral principles is gathered over the course of a relationship with the borrower. Relationship lending has been posited as the preferred methodology for banks to employ especially when engaging with small and medium enterprises (SMEs) due to the information opacity that characterizes these firms. Soft information is distinguished from hard information which is that information about a borrower which is readily available at the time of loan origination and includes financial statements and collateral. Although extant literature recognizes the importance of soft information, particularly for lending to SMEs that are characterized by high levels of opacity, it does not pay much attention to how soft information is acquired and transferred for use in making a lending decision. This study explores the process of soft knowledge acquisition and transfer for use in the SME lending decision. A qualitative multiple case study of selected commercial banks in Kenya is employed to gain an in-depth understanding of how soft information is transferred from the SME client and eventually used in making a lending decision. Data is collected through semi structured interviews conducted with SME relationship managers (RM) who work closely with SMEs and are thus able to describe the process from the onset of the relationship to disbursement of a loan. The results suggest that when considering an SME lending decision, banks make use of both soft and hard information. The relationship manager or relationship officer is the primary collector of soft information and transfers this information after verification, through the channels of the loan application process.